Expression of CDX2 and Thyroid Transcription Factor-1 in Oropharyngeal Undifferentiated Carcinomas: A Potential Diagnostic Pitfall. Issue 4 (April 2018) - Chernock, Rebecca D.; Bibbey, Scott; El-Mofty, Samir K.; Carpenter, Danielle H.; Lewis, James S.
Abstract : Oropharyngeal undifferentiated carcinomas are rare and most are human papillomavirus related. Morphologically, they overlap with undifferentiated carcinomas from other organ sites, including the nasopharynx, lung, and gastrointestinal tract. Most have lymph node metastases at presentation and, especially when initially encountered in a lymph node, immunostains may be performed to determine the most likely primary site. We recently reviewed a case in consultation that strongly and diffusely expressed both thyroid transcription factor-1 (TTF-1, SPT24 clone) and CDX2, 2 widely used markers that are considered relatively lineage specific for lung/thyroid and intestinal differentiation, respectively. Unexpected expression of these markers could be misleading. However, they have not been previously assessed in oropharyngeal undifferentiated carcinoma. Here, we performed immunohistochemistry for CDX2 and TTF-1 (8G7G3/1 clone) on primary tumors and/or lymph node metastases from 11 in-house patients with previously characterized undifferentiated carcinoma of the oropharynx from 1992 to 2008. All were male with an average age of 56.7 years, and 5 (46%) initially presented with a neck mass. All were Epstein-Barr virus negative and 9 (82%) were human papillomavirus and p16 positive. CDX2 was positive in 6 of the 11 (55%) cases. However, staining was generally weak to moderate and/or nondiffuse. TTF-1 was negative in all the in-house cases and showed only rare, weakly positive cells in the consult case when TTF-1 was repeated using the 8G7G3/1 clone. Thus, CDX2 immunoreactivity is common, whereas TTF-1 expression is rare in oropharyngeal undifferentiated carcinomas. As a result, one should not rely on CDX2 as evidence of intestinal differentiation or origin in metastatic undifferentiated carcinomas in the neck, particularly when staining is not strong and diffuse. In addition, TTF-1 should be interpreted with caution especially when using the SPT24 clone.